Regulation of complement membrane attack complex formation in myocardial infarction. - Väkevä, A. (1993)
Recent studies have suggested that the complement (C) system is involved in the development of tissue injury of myocardial infarction. As it is not known why the strictly controlled C system starts to react against autologous heart tissue, we have analyzed the expression of various membrane regulators of C (CR1, DAF, MCP, CD59, C8 binding protein) and the pattern of deposition of C components and plasma C regulators (C4b binding protein and vitronectin) in normal (n = 7) and infarcted (n = 13) human myocardium. In the infarcted myocardium deposits of the C membrane attack complex (MAC) were observed by immunofluorescence microscopy, and lesions resembling the transmembrane channels of MAC were detected by transmission electron microscopy. CD59 and C8 binding protein were strongly expressed by muscle cells of normal myocardial tissue. Little or no CR1, MCP, and DAF was observed on these cells. The assembly of MAC was accompanied by the deposition of vitronectin (S-protein) and C4b binding protein in the infarcted areas of myocardium. In accordance with our earlier results the expression of CD59 but not of C8 binding protein was clearly diminished in the lesions. The results show that C8 binding protein, vitronectin, and C4b binding protein do not prevent complement attack against the infarcted myocardium but rather become codeposited with the MAC. Ischemia-induced transformation of nonviable cells into complement activators, acquired loss of resistance to the MAC by shedding of CD59, and recruitment of multifunctional serum proteins by MAC could thus constitute a general process aimed at the clearance of injured tissue.